Youngia lushanensis, a new species of Asteraceae from Sichuan, China, inferred from morphology and nrITS phylogeny - Peng, Yulan; Pu, Xuemei; Xiong, Xianhua; Cheng, Lijie (Frontiers in Plant Science, 2024)
Youngia lushanensis (Asteraceae), a new species of Youngia, is described and illustrated from Lushan in Sichuan, Southwest China. Its systematic position is evaluated based on a molecular phylogenetic analysis of the nuclear ribosomal ITS and on morphological comparison with related species. It is morphologically similar to Y. purpimea and Y. szechuanica, with purplish red abaxially leaves. But it differs from the latter two in that its caudex are glabrous, leaf margins are sparsely dentate, and being glabrous on both surfaces, 9-11 florets in each capitulum, and inner phyllaries are crested. Phylogenetic analysis based on ITS also showed this new species is closely related with Y. purpimea and Y. szechuanica. The three species Y. lushanensis Y. purpimea and Y. szechuanica, formed a basal group of Youngia, which is distributed in moist slopes in Southwest China..